2023
DOI: 10.1038/s41598-023-34918-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of an inverted pendulum with positive position feedback controller approximate uniform solution

Abstract: The inverted pendulum is controlled in this article by using the nonlinear control theory. From classical analytical mechanics, its substructure equation of motion is derived. Because of the inclusion of the restoring forces, the Taylor expansion is employed to facilitate the analysis. An estimated satisfactory periodic solution is obtained with the aid of the modified Homotopy perturbation method. A numerical technique based on the fourth-order Runge–Kutta method is employed to justify the previous solution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…15 . It is shown that from this figure and from both Tables 1 and 2 that the analytical solution is merely reliable with the calculation path as shown earlier 15 , 30 , 42 , 48 .…”
Section: Discussion and Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…15 . It is shown that from this figure and from both Tables 1 and 2 that the analytical solution is merely reliable with the calculation path as shown earlier 15 , 30 , 42 , 48 .…”
Section: Discussion and Resultssupporting
confidence: 70%
“…Subsequently, we may indicate that the optimal mode of oscillation lessening is . Previous instances were involved 15 , 30 , 42 , 48 .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The inverted pendulum 1 , 2 is a well-known and extensively studied control problem that has attracted significant research attention due to its inherent instability and practical applications in various fields. The rotary inverted pendulum (RIP) 3 , 4 , a fascinating and extensively studied control problem, presents unique challenges due to its rotational nature.…”
Section: Introductionmentioning
confidence: 99%
“…The domain of control systems has long been a cornerstone of engineering, dating to the application of Lagrangian mechanics and Newtonian mechanics to derive the governing equations of various systems [1]- [3]. While these classical mechanics have paved the way for modern control strategies, such as Proportional-Integral-Derivative (PID) controllers, linear quadratic regulators (LQR), fuzzy logic, and neural networks, a shift toward more advanced approaches is evident [4]- [17].…”
Section: Introductionmentioning
confidence: 99%